Hadith #200 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
Anas said, “The Prophet (ﷺ) asked for water and a tumbler with a broad base and no so deep, containing a small quantity of water, was brought to him whereby he put his fingers in it.” Anas further said, ‘ noticed the water springing out from amongst his fingers.” Anas added, ‘ estimated that the people who performed ablution with it numbered between seventy to eighty.”
Grade: Sahih

Hadith #783 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
Anas used to demonstrate to us the prayer of the Prophet (ﷺ) and while demonstrating, he used to raise his head from bowing and stand so long that we would say that he had forgotten (the prostration).
Grade: Sahih

Hadith #803 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
Anas said, “I will leave no stone unturned in making you offer the prayer as I have seen the Prophet (ﷺ) making us offer it.” Anas used to do a thing which I have not seen you doing. He used to stand after the bowing for such a long time that one would think that he had forgotten (the prostrations) and he used to sit in-between the prostrations so long that one would think that he had forgotten the second prostration.
Grade: Sahih

Hadith #1316 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
The Prophet (p.b.u.h) said, “Whoever intentionally swears falsely by a religion other than Islam, then he is what he has said, (e.g. if he says, ‘If such thing is not true then I am a Jew,’ he is really a Jew). And whoever commits suicide with piece of iron will be punished with the same piece of iron in the Hell Fire.” Narrated Jundab the Prophet (ﷺ) said, “A man was inflicted with wounds and he committed suicide, and so Allah said: My slave has caused death on himself hurriedly, so
Grade: Sahih

Hadith #4636 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
who was one of the companions of the tree (those who swore allegiance to the Prophet (ﷺ) beneath the tree at Al-Hudaibiya):
Grade: Sahih

Hadith #5818 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
(who was one of the companions who gave the pledge of allegiance to the Prophet (ﷺ) underneath the tree (Al-Hudaibiya)) Allah’s Messenger (ﷺ) said, “Whoever swears by a religion other than Islam (i.e. if somebody swears by saying that he is a non-Muslim e.g., a Jew or a Christian, etc.) in case he is telling a lie, he is really so if his oath is false, and a person is not bound to fulfill a vow about a thing which he does not possess. And if somebody commits suicide with anything in this
Grade: Sahih

Hadith #5873 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whoever swears by a religion other than Islam (i.e. if he swears by saying that he is a non-Muslim in case he is telling a lie), then he is as he says if his oath is false and whoever commits suicide with something, will be punished with the same thing in the (Hell) fire, and cursing a believer is like murdering him, and whoever accuses a believer of disbelief, then it is as if he had killed him.”
Grade: Sahih

Hadith #6410 - Sahih al-Bukhari - Thabit bin 'Ubaid al-Ansari ثابت بن عبيد الأنصاري (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whoever swears by a religion other than Islam, is, as he says; and whoever commits suicide with something, will be punished with the same thing in the (Hell) Fire; and cursing a believer is like murdering him; and whoever accuses a believer of disbelief, then it is as if he had killed him.”
Grade: Sahih